Aspirin and P2Y12 inhibition attenuate platelet-induced ovarian cancer cell invasion - SHEILS, ORLA; O'LEARY, JOHN; SPILLANE, CATHY (My University, 2015)
Background: Platelet-cancer cell interactions play a key role in successful haematogenous metastasis. Disseminated malignancy is the leading cause of death among ovarian cancer patients. It is unknown why different ovarian cancers have different metastatic phenotypes. To investigate if platelet-cancer cell interactions play a role, we characterized the response of ovarian cancer cell lines to platelets both functionally and at a molecular level. Methods: Cell lines 59M and SK-OV-3 were used as in vitro model systems of metastatic ovarian cancer. Platelet cloaking of each cell line was quantified by flow cytometry. Matrigel invasion chamber assays were used to assess the invasive capacity of the cell lines. The induction of an EMT was assessed by morphology analysis and by gene expression analysis of a panel of 11 EMT markers using TaqMan RT-PCR. Results: SK-OV-3 cells adhered to and activated more platelets than 59M cells (p=0.0333). Platelets significantly promoted the ability of only SK-OV-3 cells to invade (p≤0.0001). Morphology and transcritpome analysis indicated that platelets induce an epithelial-to-mesenchymal transition phenotype in both cells lines, with a more exaggerated response in SK-OV-3 cells. Next, we investigated if antiplatelet agents could abrogate the platelet-induced aggressive phenotype in SK-OV-3 cells. Both aspirin (p≤0.05) and 2-methylthioadenosine 5'-monophosphate triethylammonium salt hydrate (P2Y12 inhibitor; p≤0.01) significantly decreased their invasion capacity, and effectively reverted invasion to levels comparable to SK-OV-3 cells alone. Conclusion: While there is increasing evidence for the cancer-protective effect of aspirin, this study suggests P2Y12 inhibition may also play a role. Understanding these complex interactions between platelets and cancer cells could ultimately allow the establishment of therapies tailored to inhibiting metastasis, thus significantly reducing cancer morbidity
PUBLISHED
Keywords: 2 methylthioadenosine 5' monophosphate triethylammonium; acetylsalicylic acid; antineoplastic agent; purinergic P2Y12 receptor; transcriptome; unclassified drug; 2 methylthioadenosine 5' monophosphate triethylammonium; acetylsalicylic acid; antineoplastic agent; purinergic P2Y12 receptor; transcriptome; unclassified drug; Cancer; CANCER; METASTASIS; PLATELETS; Health